High‐throughput sequencing of faeces provides evidence for dispersal of parasites and pathogens by migratory waterbirds. (24th December 2021) - Briscoe, Andrew G.; Nichols, Sarah; Hartikainen, Hanna; Knipe, Hazel; Foster, Rachel; Green, Andy J.; Okamura, Beth; Bass, David
Abstract: Examination of faecal material has demonstrated how a broad range of organisms are distributed by bird movements. Such research has largely focused on dispersal of plant seeds by frugivores and of freshwater organisms by waterbirds. However, with few exceptions (e.g. avian influenza, Ebola virus), there is a dearth of evidence for transport of parasites and pathogens. High‐throughput sequencing methods now provide a powerful means of addressing this knowledge gap by elucidating faecal contents in unprecedented detail. We collected faeces excreted by a range of migratory waterbirds in south‐west Spain and pooled faecal DNA to create libraries reflective of feeding behavior. We created sets of libraries using high‐throughput metagenomic and amplicon sequencing. For the latter we employed two sets of primers to broadly target the V4 region of the 18S rRNA gene (one set amplifying the region across all eukaryotes, the other excluding amplification of metazoans). Libraries revealed a wide diversity of eukaryotes, including parasites of the faecal producers themselves, parasites of food items, or those incidentally ingested. We also detected novel microbial eukaryotic taxa and found that parasite assemblage profiles were relatively distinct. Comparing the performance of the methods used supports their joint use for future studies of diversity and abundance. Because viable stages of many parasites are likely to be present in faeces, our results suggest significant levels of bird‐mediated dispersal of parasites (both from avian and other hosts). Our methods revealed much hidden biodiversity, and allowed identification of the individuals who produced the faecal samples to species level, facilitating the study of interaction networks.